1993
DOI: 10.1111/j.1432-1033.1993.tb17690.x
|View full text |Cite
|
Sign up to set email alerts
|

Study of the states and populations of the rat pancreatic cholecystokinin receptor using the full peptide antagonist JMV 179

Abstract: The full peptide antagonist of the pancreatic cholecystokinin (CCK) receptor, JMV 179, [BocTyr(S0,H)-Ahx-Gly-dTrp-Ahx-Asp phenylethyl ester, where Tyr(S0,H) = sulfated tyrosine, Ahx = 6-aminohexanoic acid] was modified at its N-terminus by incorporation of p-hydroxyphenyl propionate (Bolton-Hunter reagent, BH) and was subsequently radioiodinated. After HPLC purification, lZ51-BH-JMV-179, a CCK antagonist radioligand of high specific activity (2000 CUmmol) was obtained. '251-BH-JMV-179 bound to a single populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
5
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 43 publications
5
5
0
Order By: Relevance
“…All these states were, however, bound with high affinity by an antagonist, resulting in a larger fraction of CCK 1 receptor states with high affinity for the antagonist than for the agonist. Accordingly, radiolabeled CCK 1 receptor antagonists labeled considerably more CCK 1 receptor binding sites in the rat pancreas compared with CCK 1 receptor agonists 31, 32. The present study indicates that the same is true for human CCK 1 receptors expressed in tumors.…”
Section: Discussionsupporting
confidence: 58%
“…All these states were, however, bound with high affinity by an antagonist, resulting in a larger fraction of CCK 1 receptor states with high affinity for the antagonist than for the agonist. Accordingly, radiolabeled CCK 1 receptor antagonists labeled considerably more CCK 1 receptor binding sites in the rat pancreas compared with CCK 1 receptor agonists 31, 32. The present study indicates that the same is true for human CCK 1 receptors expressed in tumors.…”
Section: Discussionsupporting
confidence: 58%
“…Therefore, the receptor‐binding affinity of an agonist measured as competition of an agonist‐based radioligand would be higher than that measured with an antagonist‐based radioligand, whereas antagonists should display comparable affinities, as was observed in our study. Similar observations were reported from binding studies on the rat pancreatic CCK‐A receptor using a CCK antagonist radioligand (41).…”
Section: Discussionsupporting
confidence: 84%
“…In addition to the biphasic nature of the saturation binding isotherm, it was also observed that the slope of the competition–inhibition curve for L‐364,718 was significantly greater than unity in the assays of both the canine and human CCK1 receptor. This finding is not unique as steep Hill slopes have been previously reported for L‐364,718 in rat pancreatic tissue (Silvente Poirot et al ., 1993; n H =2.01, p K I =9). Interestingly, the slope for L‐364,718 was not steep when measured at the canine CCK2 receptor although, due to the 10‐fold lower affinity for this receptor, the competition–inhibition curve was obtained over a higher concentration range.…”
Section: Discussionsupporting
confidence: 79%